2014
DOI: 10.1111/bjh.12828
|View full text |Cite
|
Sign up to set email alerts
|

MiRNome expression is deregulated in the peripheral lymphoid compartment of multiple myeloma

Abstract: SummaryMicroRNAs (miRNAs) are short non-coding RNAs involved in the regulation of gene expression. Selected groups of miRNAs are differentially expressed in various types of cancers. Alterations in miRNAs gene expression have been shown in cells from the B-cell malignancy, multiple myeloma (MM). However, although MM is a disease of plasma cells, abnormalities have been detected in the peripheral blood of the patients. The goal of our study was to analyse the entire miRNome in peripheral lymphocytes of MM patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…One report of circulating miRNA in MM identified let-7e and miR-744 as critical to differentiate from normal as well as correlate with overall survival, but this was based on a discovery set of just 13 patients 12 . A study of PBMCs from only 5 MM patients found numerous differences compared to 5 healthy controls 13 , but the small sample size limits generalizability.…”
Section: To the Editormentioning
confidence: 99%
“…One report of circulating miRNA in MM identified let-7e and miR-744 as critical to differentiate from normal as well as correlate with overall survival, but this was based on a discovery set of just 13 patients 12 . A study of PBMCs from only 5 MM patients found numerous differences compared to 5 healthy controls 13 , but the small sample size limits generalizability.…”
Section: To the Editormentioning
confidence: 99%
“…Finally, miRNAs have been implicated in the pathogenesis of MM [ 100 ]. Li et al evaluated the role of miR-15a/16 in the pathogenesis of MM.…”
Section: Proinflammatory Cytokinesmentioning
confidence: 99%
“…In previous works, we have demonstrated the presence of a modified microRNA signature in the peripheral lymphoid compartment of MM subjects and MM patients with BONJ [29,30].…”
Section: Introductionmentioning
confidence: 85%